A sodium iron fluorophosphate pyrophosphate positive electrode material, a preparation method and application thereof
Patent Information
- Application Number
- CN202510844527.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-23
- Publication Date
- 2026-09-22
- Estimated Expiration
- 2045-06-23
AI Technical Summary
[0004]鉴于上述的分析,本发明实施例旨在提供一种氟代磷酸焦磷酸铁钠正极材料及其制备方法和应用,用以解决现有技术中氟代磷酸焦磷酸铁钠类材料制备过程中氟取代困难、易产生环境污染、综合性能不佳等问题中的至少一个
[0028]2、本发明所提供的氟代磷酸焦磷酸铁钠正极材料(或制成的正极极片)充放电过程中的体积变化小,氟的共价半径为71pm,氧的共价半径为73pm,氟取代氧可以有效收缩晶格,减小晶体结构在充放电过程中的体积变化。氟取代焦磷酸根(P2O74-)中的氧,由于P-F键的键能高于P-O键,因此结构更加稳定。同时,充放电过程中焦磷酸根扭曲所导致的相变可以得到有效抑制。利用氟的强电负性,通过诱导效应可以提升氧化还原电势,从而提升电池的工作电位。氟取代只会改变阴离子基团的组成,金属活性中心的数量不变,因此材料的理论容量可以提升。
Smart Images

Figure CN121149174B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery technology, and in particular to a sodium iron fluorinated phosphate pyrophosphate cathode material, its preparation method, and its application. Background Technology
[0002] The 21st century is a crucial stage in the global energy system transformation. The increasing energy demand and growing emphasis on environmental protection have made clean and renewable energy a hot topic in research and development. However, clean energy sources such as wind and solar power require large-scale energy storage devices due to their discontinuous supply. Considering factors such as safety and resource costs, sodium-ion battery systems have promising application prospects. In sodium-ion batteries, the design of the cathode material is crucial. Currently, common cathode materials for sodium-ion batteries include polyanionic, layered oxides, and Prussian blue analogs. Among them, polyanionic cathode materials, with their stable anionic framework structure, exhibit smaller volume changes during charge and discharge, giving them an advantage in cycle performance compared to the other two types of materials. Among polyanionic materials, iron-based materials, represented by sodium iron pyrophosphate (NFPP), can fully leverage the cost advantage of sodium-ion batteries. However, NFPP faces challenges such as poor electronic conductivity, low operating potential, and distortion of the crystal structure at the end of charging.
[0003] Anionic substitution is an effective means to solve the above problems. The introduction of fluorine can not only improve intrinsic electronic conductivity by reducing the band gap of the material, but also increase the redox potential by increasing the inductive effect of anionic groups through strong electronegativity, while shortening the covalent distance to suppress structural distortion. In existing published patents and papers, the introduction of fluorine is achieved by using sodium fluoride as the fluorine source, which has the following problems: First, from a thermodynamic point of view, the literature reports that fluorine substitution of oxygen in phosphate is not energy-efficient, and it is difficult to obtain the substitution product by using fluoride ions as a precursor, resulting in low efficiency; second, in acidic environments, fluoride ions will combine with hydrogen ions to form hydrogen fluoride and escape from the system, which is environmentally harmful. Summary of the Invention
[0004] In view of the above analysis, the present invention aims to provide a sodium iron pyrophosphate cathode material of fluorophosphate, its preparation method and application, so as to solve at least one of the problems in the preparation process of sodium iron pyrophosphate fluorophosphate materials in the prior art, such as difficulty in fluorine substitution, easy generation of environmental pollution and poor overall performance.
[0005] This invention provides a sodium iron fluorinated phosphoric acid pyrophosphate cathode material, the cathode material comprising an amorphous carbon coating layer and a sodium iron fluorinated phosphoric acid pyrophosphate core;
[0006] The molecular formula of the sodium ferric fluoride pyrophosphate is Na. 4+z Fe 3-y(PO4)2P2O 7-x F 2x ;
[0007] Where x takes values of: 0 < x ≤ 1, y takes values of: 0 ≤ y ≤ 0.15, and z takes values of: -0.4 ≤ z ≤ 0.4.
[0008] Specifically, the space group of the crystal structure of the sodium ferric fluoride pyrophosphate is Pn21a, which belongs to the orthorhombic crystal system;
[0009] The range of unit cell parameters is: α = β = γ = 90°;
[0010] Where a, b, and c are the cell lengths along the three-dimensional coordinate axes, and α, β, and γ are the angles between each pair of them.
[0011] Specifically, the sodium fluorinated phosphate pyrophosphate has the same basic structural framework and crystallographic symmetry as sodium phosphate pyrophosphate or its iron-deficient phase;
[0012] The structural difference of the sodium ferric fluoride pyrophosphate is that two fluorine atoms replace one oxygen atom in the pyrophosphate ditetrahedron.
[0013] Specifically, the bonding characteristics of the sodium ferric pyrophosphate are as follows: fluorine atoms and iron atoms do not form direct bonds, but fluorine atoms form bonds with phosphorus atoms in the pyrophosphate group.
[0014] Specifically, the mass fraction of the amorphous carbon coating layer is 1–5 wt.%.
[0015] This invention discloses a method for preparing the aforementioned cathode material, specifically comprising the following steps:
[0016] S1: Mix the precursor of sodium ferric fluoride pyrophosphate and prepare it into a powder;
[0017] S2: The powder obtained in S1 is calcined at high temperature and then sieved to obtain sodium iron pyrophosphate cathode material.
[0018] Specifically, the precursor of the sodium ferric fluoride pyrophosphate includes a sodium source, an iron source, a phosphorus source, a fluorine source, and a carbon source;
[0019] The molar ratio of sodium, iron, phosphorus, and fluorine in the raw materials is 3.9–4.1:3-y:4:2x.
[0020] The amount of carbon source added depends on the carbonization rate, ensuring that the mass fraction of carbon in the final product is 1-5 wt.%.
[0021] Specifically, step S1 employs one of the following processes: solid-phase ball milling, sol-gel method, or "liquid-phase sand milling + spray drying".
[0022] Specifically, the high-temperature calcination steps in step S2 are as follows:
[0023] In the tube furnace, the gas atmosphere is controlled to be nitrogen, argon, or a hydrogen-argon mixture, the gas flow rate is 50-200 mL / min, the heating rate is set to 2-5℃ / min, the holding temperature is 450-600℃, and the holding time is 5-12 h; the cooling process is natural cooling, and the cooling rate is controlled to be ≤5℃ / min.
[0024] The present invention also discloses a sodium-ion battery, the battery comprising the positive electrode material described above or the positive electrode material prepared by the preparation method described above.
[0025] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0026] 1. The sodium iron fluorinated phosphoric acid pyrophosphate cathode material provided by this invention has good charge / discharge capacity, rate performance, and cycle performance, and the reversible specific capacity of the prepared cathode sheet is significantly improved. The cathode material (mainly sodium iron fluorinated phosphoric acid pyrophosphate) prepared by this invention has a phase purity of ≥95%. When the cathode material provided by this invention is used to prepare the electrode and assembled with sodium metal in a half cell, the test voltage range is 1.5~4.3V, the specific capacity of the first charge at 0.1C is ≥122mAh / g, the specific capacity of the first discharge at 0.1C is ≥115mAh / g, the coulombic efficiency is ≥93.5%, the reversible specific capacity at 10C is ≥89mAh / g, and the capacity retention rate at 1C-1000 cycles is ≥98.8%.
[0027] The increased capacity of the material is attributed to the improved phase purity resulting from fluorine substitution, allowing the actual capacity to more closely approximate the theoretical capacity. The improved rate performance is primarily due to the reduced band gap after fluorine substitution, which enhances the intrinsic electronic conductivity. Simultaneously, the higher PF bond energy strengthens the structural stability during charge and discharge, suppresses lattice distortion, and thus improves the sodium ion diffusion coefficient. The improved cycle life is attributed to a significant reduction (approximately 50%) in changes in cell parameters during cycling, suppressing lattice mismatches that may occur during lattice contraction and expansion, thereby extending cycle life.
[0028] 2. The sodium iron pyrophosphate fluorinated phosphoric acid cathode material (or the cathode sheet made therefrom) provided by this invention exhibits small volume change during charge and discharge. The covalent radius of fluorine is 71 pm, and that of oxygen is 73 pm. Fluorine substitution for oxygen effectively shrinks the crystal lattice, reducing the volume change of the crystal structure during charge and discharge. Fluorine substitution of pyrophosphate (P₂O₇) 4-The oxygen in the PF bond is more stable due to the higher bond energy of the PO bond. Simultaneously, the phase transition caused by pyrophosphate distortion during charging and discharging can be effectively suppressed. Utilizing the strong electronegativity of fluorine, the redox potential can be increased through an inductive effect, thereby enhancing the battery's operating potential. Fluorine substitution only alters the composition of the anionic groups; the number of metal active centers remains unchanged, thus increasing the material's theoretical capacity.
[0029] It is worth noting that the fluorine substitution strategy in this invention has shown effectiveness in many phosphate, pyrophosphate, and mixed phosphate materials. In particular, due to the unique characteristic of sodium iron pyrophosphate being connected between layers by pyrophosphate ions, fluorinated sodium iron pyrophosphate exhibits a more significant improvement in electrochemical performance because fluorine substitution effectively suppresses its distortion.
[0030] 3. This invention provides a method for preparing sodium iron fluoride pyrophosphate from phosphorus-containing fluorine bond (PF) compounds. The precursor can effectively provide PF bonds, ensuring a high success rate of fluorination. As shown in Comparative Example 2, the utilization rate of fluorine in this invention can reach over 90%, while the utilization rate of fluorine in existing technologies is only around 20%. The preparation method can effectively inhibit the combination of free fluoride ions and hydrogen ions in solution to form toxic hydrogen fluoride.
[0031] It is worth emphasizing that the advantage of this preparation method lies in avoiding the process of fluoride ions replacing oxygen ions in phosphate or pyrophosphate groups. This process has a high reaction energy barrier because its specific steps include: phosphate ions combining with protons to form (O3P-OH). 2- Structure, then F - Attack P, causing OH - The substitution reaction occurs after the fluoride ion is removed. The substitution step has a high energy barrier, limiting its progress and making fluorination using fluoride ions as precursors very difficult. This problem is solved by introducing compounds containing PF bonds.
[0032] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0033] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0034] Figure 1A schematic diagram of the crystal structure of sodium iron pyrophosphate cathode material with fluorophosphate.
[0035] Figure 2 The X-ray diffraction pattern of sodium ferric fluoride pyrophosphate prepared in Example 1;
[0036] Figure 3 This is a scanning electron microscope image of sodium ferric fluoride pyrophosphate in Example 2;
[0037] Figure 4 The energy dispersive spectrum of elements in sodium iron fluoride pyrophosphate in Example 3;
[0038] Figure 5 Sodium ferric fluoride pyrophosphate in Example 4 19 F nuclear magnetic resonance spectrum;
[0039] Figure 6 The 0.1C charge-discharge curve of the sodium iron pyrophosphate half-cell assembled in Example 1 of the present invention and its comparison with sodium iron pyrophosphate in Comparative Example 1 are shown.
[0040] Figure 7 Rate performance of the sodium iron pyrophosphate half-cell assembled in Example 3.
[0041] Figure 8 Cyclic performance of the sodium iron pyrophosphate half-cell assembled in Example 4. Detailed Implementation
[0042] Preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which form part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0043] Based on extensive preliminary research, experimental exploration, and summarization, this invention summarizes the following technical challenges and proposes possible solutions / ideas:
[0044] (1) In order to solve the problem of fluorine substitution difficulties in existing preparation technologies, a preparation technology using phosphorus-containing fluorine bond compounds (PF) as precursor fluorine sources is proposed to ensure the success rate of fluorination of phosphate and pyrophosphate.
[0045] (2) In order to solve the problem of hydrogen fluoride escape in the existing preparation technology, the use of fluorine source that ionizes into free fluoride ions in solution is avoided, and the system is controlled to be near neutral or weakly alkaline to ensure that the preparation process is efficient and safe.
[0046] (3) A series of new fluorophosphate iron sodium pyrophosphate compositions are proposed, and substances composed of these compositions can be used as novel cathode materials for sodium-ion batteries. Their molecular formula is Na. 4+zFe 3-y (PO4)2P2O 7-x F 2x The values of x range from 0 to 1, y from 0 to 0.15, and z from -0.4 to 0.4. This compound is characterized by stronger PF bond energies, resulting in a more stable polyanionic framework system. Its specific crystal structure is shown in the attached figure. Figure 1 As shown, replacing the oxygen in the pyrophosphate group with fluorine can suppress the distortion of the group in the final state of charging, enhance structural stability, improve cycle life, and enhance the sodium ion diffusion coefficient. Simultaneously, fluorine substitution reduces the band gap and improves electronic conductivity. Therefore, the material described in this invention has a longer cycle life and rate capability compared to similar non-fluorinated materials.
[0047] In summary, compared with traditional sodium iron pyrophosphate materials, the sodium iron pyrophosphate cathode designed in this invention exhibits improvements in both structural stability and electrochemical performance. The structural stability is primarily manifested in thermal and cycling stability, thanks to the fluorine substitution suppressing the distortion of the pyrophosphate groups, thereby reducing internal crystal stress. Simultaneously, the higher PF bond energy enhances the framework stability, effectively increasing the decomposition temperature and improving safety. The improved electrochemical performance is mainly reflected in increased rate capability and longer cycle life. This is primarily due to the fluorine substitution reducing the band gap of the material, thereby enhancing electronic conductivity, and simultaneously suppressing lattice mismatch caused by crystal structure contraction and expansion during cycling.
[0048] This invention provides a sodium iron fluorinated phosphoric acid pyrophosphate cathode material, the cathode material comprising an amorphous carbon coating layer and a sodium iron fluorinated phosphoric acid pyrophosphate core;
[0049] The molecular formula of the sodium ferric fluoride pyrophosphate is Na. 4+z Fe 3-y (PO4)2P2O 7-x F 2x ;
[0050] Where x takes values of: 0 < x ≤ 1, y takes values of: 0 ≤ y ≤ 0.15, and z takes values of: -0.4 ≤ z ≤ 0.4.
[0051] Specifically, the space group of the crystal structure of the sodium iron fluorinated phosphate is Pn21a, which belongs to the orthorhombic crystal system, such as... Figure 1 As shown, in the structure, FeO6 octahedrons and PO4 tetrahedrons are connected by sharing edges or vertices, forming [Fe3P2O] parallel to the bc plane. 13 The layers are interconnected along the a-axis by [P2O6F].
[0052] The range of unit cell parameters is: α = β = γ = 90°;
[0053] Where a, b, and c are the unit cell lengths along the three-dimensional coordinate axes, and α, β, and γ are the angles between each pair of these axes. Because fluorine has a smaller radius than oxygen and is more electronegative, it significantly shortens the unit cell length. The PF bond energy is also smaller, improving stability.
[0054] Specifically, the sodium fluorinated phosphate pyrophosphate has the same basic structural framework and crystallographic symmetry as sodium phosphate pyrophosphate or its iron-deficient phase;
[0055] The structural difference of the sodium iron fluorinated phosphate pyrophosphate lies in the fact that two fluorine atoms replace one oxygen atom in the pyrophosphate ditetrahedron. This substitution enhances bond energy, improves the pyrophosphate distortion at the final state of charging, thereby reducing lattice distortion and decreasing lattice mismatch during cycling, thus improving cycling stability and sodium ion diffusion characteristics.
[0056] Specifically, the bonding characteristics of the aforementioned sodium ferric phosphate pyrophosphate are as follows: fluorine atoms and iron atoms do not form direct bonds, but rather fluorine atoms form bonds with phosphorus atoms in the pyrophosphate group. This characteristic is brought about by the PF bond precursor; the inhibition of Fe-F bond formation allows the structure of sodium ferric phosphate pyrophosphate to be maintained, avoiding drastic structural changes.
[0057] Specifically, the mass fraction of the amorphous carbon coating layer is 1–5 wt.%. The function of the carbon coating layer is to improve the electronic conductivity of the material, while limiting the excessive growth of particles during the sintering process, and to reduce trivalent iron to divalent iron via carbothermic reduction.
[0058] This invention discloses a method for preparing the aforementioned cathode material, the main feature of which is that: fluorophosphoric acid or fluorophosphate is used as the precursor fluorine source, so that the phosphorus-fluorine chemical bond exists in the system from the beginning, reducing the difficulty of fluorine substitution product formation, and inhibiting the combination of free fluoride ions with hydrogen ions in the solution to form hydrogen fluoride and escape.
[0059] Specifically, the following steps are included:
[0060] S1: Mix the precursor of sodium ferric fluoride pyrophosphate and prepare it into a powder;
[0061] S2: The powder obtained in S1 is calcined at high temperature and then sieved to obtain sodium iron pyrophosphate cathode material.
[0062] Specifically, the pH of the precursor mixture (liquid) in S1 is controlled at near neutral or weakly alkaline, with a specific value range of 5.5-9.0.
[0063] Specifically, the precursor of sodium iron pyrophosphate described in S1 includes sodium source, iron source, phosphorus source, fluorine source and carbon source;
[0064] The molar ratio of sodium:iron:phosphorus:fluorine in the raw materials is 3.9–4.1:3y:4:2x. The amount of carbon source added depends on the carbonization rate, ensuring that the mass fraction of carbon in the final product is 1–5 wt.%. For each set of x and y values, the proportion of the latter three elements is fixed, but the proportion of sodium can be excessive or insufficient, adjusted according to the performance of the prepared product.
[0065] The sodium source includes at least one of sodium dihydrogen phosphate, disodium hydrogen phosphate, sodium phosphate, sodium carbonate, sodium bicarbonate, sodium acetate, sodium oxalate, sodium monofluorophosphate, sodium pyrophosphate, and disodium dihydrogen pyrophosphate.
[0066] The iron source includes at least one of ferric nitrate, ferrous oxalate, ferric oxide red, ferric oxide yellow, ferric phosphate, ferric citrate, and ferrous phosphate;
[0067] Phosphorus sources include at least one of phosphoric acid, diammonium dihydrogen phosphate, diammonium hydrogen phosphate, and sodium-containing phosphates mentioned above;
[0068] The fluorine source includes at least one of monofluorophosphate, difluorophosphate, sodium monofluorophosphate, sodium difluorophosphate, sodium hexafluorophosphate, ammonium monofluorophosphate, and sodium iron fluorophosphate. Using fluorophosphate or fluorophosphate as the precursor fluorine source ensures that the phosphorus-fluorine chemical bond exists in the system from the beginning, reducing the difficulty of fluorine substitution product formation and inhibiting the combination of free fluoride ions with hydrogen ions in the solution to form hydrogen fluoride and escape.
[0069] The carbon source includes at least one of the pyrolytic carbon sources such as glucose, sucrose, starch, ascorbic acid, and citric acid.
[0070] Specifically, step S1 employs one of the following processes: solid-phase ball milling, sol-gel method, or "liquid-phase sand milling + spray drying".
[0071] The specific steps of the solid-phase ball milling method are as follows:
[0072] First, weigh the precursor material according to the specified ratio and place it in a zirconia ball mill jar, along with zirconia grinding beads, wherein the mass ratio of grinding beads to material is 4–20:1. Then, dry-mill the material at a speed of 200–400 r / min for 2–6 h. After dry milling, add a grinding aid to the jar and continue milling at 200–400 r / min for 6–10 h. Finally, remove the milled material and dry it in an oven at 80–105℃, collecting the powder for further processing. Anhydrous ethanol or acetone can be used as the grinding aid.
[0073] The specific steps of the sol-gel method are as follows:
[0074] First, iron source and carbon source are prepared into solution or dispersion 1, and sodium source, phosphorus source and fluorine source are prepared into solution or dispersion 2.
[0075] Subsequently, solution 2 was slowly added to solution 1. After the addition was complete, the mixture was stirred at a constant temperature of 70–90°C for 2–4 hours, and the solvent was evaporated at the same temperature to obtain a gel.
[0076] Further heating in a vacuum oven at 100–140°C removes the water from the gel, forming a dry gel. The dry gel is then ground into powder in an agate mortar for further processing.
[0077] The solvent can be deionized water, ethanol, or a mixture of both.
[0078] The specific steps of the "liquid phase sand milling + spray drying method" are as follows:
[0079] First, the precursor material is weighed and dispersed in deionized water at a solid-liquid ratio of 0.1–0.4. The mixture is then milled in a sand mill at a power of 1500–3000 r / min for 4–10 hours. The milled mixture is then granulated by spray drying. The inlet air temperature is controlled at 200–240℃, the outlet air temperature at 80–110℃, the feed rate at 2–10 mL / min, and the atomizer speed at 18000–22000 r / min. The resulting powder is collected and passed through a 100–200 mesh sieve for further processing.
[0080] The secondary particles (aggregates of multiple small single-crystal particles) obtained by spray drying are spherical with a particle size distribution of 2–20 μm, while the primary particles (small single-crystal particles) have a particle size distribution of 50–200 nm. The primary particles have an amorphous carbon coating layer on their surface.
[0081] Specifically, the high-temperature calcination steps in step S2 are as follows:
[0082] In the tube furnace, the gas atmosphere is controlled to be nitrogen, argon, or a hydrogen-argon mixture, the gas flow rate is 50-200 mL / min, the heating rate is set to 2-5℃ / min, the holding temperature is 450-600℃, and the holding time is 5-12 h; the cooling process is natural cooling, and the cooling rate is controlled to be ≤5℃ / min.
[0083] In this process, excess components in the precursor decompose into gases and leave with the gas flow, while the remaining components generate thermodynamically stable products. Simultaneously, the organic carbon source forms an amorphous carbon layer on the surface of the generated particles, which not only improves the electronic conductivity of the final product but also restricts particle growth and reduces particle size.
[0084] The present invention also discloses a sodium-ion battery, the battery comprising the positive electrode material described above or the positive electrode material prepared by the preparation method described above.
[0085] For example, a sodium-ion battery positive electrode and battery assembly process are as follows:
[0086] 1) Preparation of the positive electrode of sodium-ion battery.
[0087] The sodium iron pyrophosphate cathode material and conductive agent are ground and mixed to ensure full contact. Then, PVDF binder and 1-methyl-2-pyrrolidone solvent are added and mixed evenly to form a slurry with a certain fluidity. The slurry is then coated onto aluminum foil or carbon-coated aluminum foil and dried in a vacuum oven at 105–120°C for 12–24 hours. The dried electrode sheets are removed, compacted using a roller press, and then cut and weighed for assembly into sodium-ion batteries. The conductive agent contains at least one of acetylene black, Super P, KS-6 graphite, and Ketjen black.
[0088] 2) Assembly and testing of sodium-ion batteries.
[0089] Using the prepared sodium ferric fluoride pyrophosphate as the positive electrode and sodium metal sheet or hard carbon as the negative electrode, a battery was assembled and its performance was tested.
[0090] The electrolyte is a common ester-based or ether-based electrolyte, including but not limited to the following formulations:
[0091] 1M NaClO4 in EC:PC=1:1Vol%with 5%FEC;
[0092] Or 1M NaPF6 in DMC:EC = 1:1 Vol%.
[0093] Or 1M NaCF3SO3 in TRIGLYME=100Vol%;
[0094] Or 1M NaTFSI in TETRAGLYME = 100 Vol%.
[0095] To maintain consistency, both the examples and comparative tests used 1M NaClO4 in EC:PC = 1:1 Vol% with 5% FEC as the electrolyte.
[0096] Example 1
[0097] First, weigh 0.05 mol ferrous oxalate dihydrate, 0.10 mol ferric phosphate dihydrate, 0.016 mol sodium hexafluorophosphate, and 5 g glucose monohydrate, and place them in a zirconia ball mill jar. The mass of the grinding beads is 200 g. Grind at 250 rpm for 2 hours. Then, add 50 mL of anhydrous ethanol and continue grinding at 300 rpm for 6 hours. After grinding, dry in an 80℃ forced-air oven and collect the powder. In a tube furnace under a nitrogen atmosphere, heat to 500℃ at a rate of 2℃ / min, hold at 500℃ for 12 hours, and then allow to cool naturally.
[0098] The X-ray diffraction pattern of the obtained powder is as follows Figure 2 As shown.
[0099] An electrode was prepared by coating the active material as the positive electrode material, and a half-cell was assembled with sodium metal. The voltage range was tested from 1.5 to 4.3 V, and a reversible specific capacity of 117 mAh / g was obtained. Figure 6 As shown.
[0100] Example 2
[0101] Compared with Example 1, the difference lies in the raw materials used, and the sintering temperature and time.
[0102] First, weigh 0.005 mol of iron oxide red, 0.02 mol of anhydrous ferric phosphate, 0.0032 mol of hexafluorophosphate, 0.02 mol of sodium carbonate, and 1 g of sucrose, and place them in a zirconia ball mill jar. The mass of the grinding beads is 200 g. Grind at 250 rpm for 2 hours. Then, add 50 mL of anhydrous ethanol and continue grinding at 300 rpm for 6 hours. After grinding, dry in an 80℃ forced-air oven and collect the powder. In a tube furnace under a nitrogen atmosphere, heat to 550℃ at a rate of 3℃ / min, hold at 550℃ for 6 hours, and then allow to cool naturally.
[0103] Scanning electron microscope images of the obtained powder are as follows: Figure 3 As shown, the particle size is between 50 and 150 nm.
[0104] The material properties obtained from assembling a sodium half-cell show a reversible specific capacity of 118 mAh / g.
[0105] Example 3
[0106] Compared with Example 1, the main difference lies in the different process of precursor treatment.
[0107] First, weigh 0.05 mol ferric citrate, 0.10 mol ferric phosphate dihydrate, 0.016 mol sodium hexafluorophosphate, and 5 g citric acid monohydrate, and disperse them in 400 mL of deionized water. The mixture was then milled using a sand mill at 2000 rpm for 6 hours. The slurry was then removed and spray-dried while stirring. The inlet air temperature was 220°C, the outlet air temperature was 80°C, the rotary atomizer speed was 18000 rpm, and the peristaltic pump feed rate was 8.0 mL / min. The dried particles were collected and heated to 600°C at a rate of 3°C / min in a tube furnace under a nitrogen atmosphere, held at 600°C for 10 hours, and then allowed to cool naturally.
[0108] The energy dispersion diagram of the obtained sodium ferric fluoride pyrophosphate is as follows: Figure 4 As shown, all elements, including fluorine, are uniformly distributed in the system, proving the feasibility of the preparation.
[0109] The obtained materials were used to assemble a half-cell, which showed a reversible specific capacity of 119 mAh / g at 0.1C and a specific capacity of 90 mAh / g at 20C rate. Figure 7 As shown.
[0110] Example 4
[0111] Compared with Example 1, the main difference lies in the different process of precursor treatment.
[0112] First, weigh 0.05 mol ferrous acetate, 0.10 mol anhydrous ferric phosphate, 0.016 mol sodium hexafluorophosphate, and 5 g sucrose, disperse them in 200 mL deionized water, add 5 mL ethylene glycol, and evaporate the solvent to dryness in an 80°C water bath with stirring to form a gel. Continue drying in a 120°C vacuum oven to obtain a dry gel, and grind it into powder. In a tube furnace under a nitrogen atmosphere, heat to 500°C at a rate of 2°C / min, hold at 500°C for 12 h, and then allow to cool naturally.
[0113] The 19F nuclear magnetic resonance spectrum of the obtained sample is as follows: Figure 5 As shown, fluorine exists in a variety of chemical environments, proving that fluorine is introduced into the crystal structure.
[0114] Using hard carbon as the negative electrode and sodium iron pyrophosphate as the positive electrode, a full cell was assembled. Electrochemical performance was tested, and the capacity retention was 98.18% after 1300 cycles at 1C. Figure 8 As shown.
[0115] Example 5
[0116] Compared with Example 1, the main difference lies in the different fluorine content in the prepared product.
[0117] Weigh out 0.05 mol of ferric oxide yellow, 0.10 mol of ferric phosphate dihydrate, 0.01 mol of sodium hexafluorophosphate, 0.02 mol of sodium pyrophosphate, and 5 g of glucose monohydrate, and place them in a zirconia ball mill jar. The mass of the milling beads is 200 g. Grind at 250 rpm for 2 hours. Then, add 50 mL of anhydrous ethanol and continue grinding at 300 rpm for 6 hours. After grinding, dry in an 80℃ forced-air oven and collect the powder. In a tube furnace under a nitrogen atmosphere, heat to 500℃ at a rate of 2℃ / min, hold at 500℃ for 12 hours, and then allow to cool naturally.
[0118] Electrodes were prepared by coating the active material as the positive electrode material, and half-cells were assembled with sodium metal. The voltage range was tested from 1.5 to 4.3 V, and a reversible specific capacity of 115 mAh / g was obtained.
[0119] Example 6
[0120] Compared with Example 1, the main difference is that the iron content in the prepared product is reduced, which introduces iron defects.
[0121] Weigh out 0.0475 mol of ferrous oxalate dihydrate, 0.10 mol of ferric phosphate dihydrate, 0.01 mol of sodium hexafluorophosphate, 0.02 mol of sodium pyrophosphate, and 5 g of glucose monohydrate, and place them in a zirconia ball mill jar. The mass of the milling beads is 200 g. Grind at 250 rpm for 2 hours. Then, add 50 mL of anhydrous ethanol and continue grinding at 300 rpm for 6 hours. After grinding, dry in an 80℃ forced-air oven and collect the powder. In a tube furnace under a nitrogen atmosphere, heat to 500℃ at a rate of 2℃ / min, hold at 500℃ for 12 hours, and then allow to cool naturally.
[0122] Electrodes were prepared by coating the active material as the positive electrode material, and half-cells were assembled with sodium metal. The voltage range was tested from 1.5 to 4.3 V, and a reversible specific capacity of 120 mAh / g was obtained.
[0123] Example 7
[0124] The main difference compared to Example 1 is that a sodium-rich sample was prepared.
[0125] First, weigh 0.05 mol ferric nitrate nonahydrate, 0.10 mol ferric phosphate dihydrate, 0.016 mol sodium hexafluorophosphate, 0.01 mol sodium bicarbonate, and 5 g sucrose, and place them in a zirconia ball mill jar. The mass of the grinding beads is 200 g. Grind at 250 rpm for 2 hours. Then, add 50 mL of anhydrous ethanol and continue grinding at 300 rpm for 6 hours. After grinding, dry in an 80℃ forced-air oven and collect the powder. In a tube furnace under a nitrogen atmosphere, heat to 500℃ at a rate of 2℃ / min, hold at 500℃ for 12 hours, and then allow to cool naturally.
[0126] Electrodes were prepared by coating the active material as the positive electrode material, and half-cells were assembled with sodium metal. The voltage range was tested from 1.5 to 4.3 V, and a reversible specific capacity of 119 mAh / g was obtained.
[0127] Example 8
[0128] The main difference compared to Example 1 is that a sodium-poor sample was prepared.
[0129] First, weigh 0.05 mol ferrous oxalate dihydrate, 0.10 mol anhydrous ferric phosphate, 0.0015 mol sodium hexafluorophosphate, 0.01 mol monofluorophosphate, and 5 g citric acid monohydrate, and place them in a zirconia ball mill jar. The mass of the grinding beads is 200 g. Grind at 250 rpm for 2 hours. Then, add 50 mL of anhydrous ethanol and continue grinding at 300 rpm for 6 hours. After grinding, dry in an 80℃ forced-air oven and collect the powder. In a tube furnace under a nitrogen atmosphere, heat to 500℃ at a rate of 2℃ / min, hold at 500℃ for 12 hours, and then allow to cool naturally.
[0130] Electrodes were prepared by coating the active material as the positive electrode material, and half-cells were assembled with sodium metal. The voltage range was tested from 1.5 to 4.3 V, and a reversible specific capacity of 118 mAh / g was obtained.
[0131] Comparative Example 1
[0132] In this comparative example, the objective is to synthesize a non-fluorinated sodium iron pyrophosphate material and compare its performance with that of the fluorinated sodium iron pyrophosphate material prepared in this invention.
[0133] First, weigh 0.05 mol ferrous oxalate dihydrate, 0.10 mol ferric phosphate dihydrate, 0.10 mol sodium dihydrogen phosphate, 0.05 mol sodium carbonate, and 5 g glucose monohydrate, and disperse them in 400 mL of deionized water. The mixture was then milled using a sand mill at 2000 rpm for 6 hours. The slurry was then removed and spray-dried while stirring. The inlet air temperature was 220°C, the outlet air temperature was 80°C, the rotary atomizer speed was 18000 rpm, and the peristaltic pump feed rate was 8.0 mL / min. The dried particles were collected and heated to 500°C at a rate of 3°C / min in a tube furnace under a nitrogen atmosphere, held at 500°C for 10 hours, and then allowed to cool naturally.
[0134] The active material used in this example was used as a positive electrode material to prepare an electrode. When it was assembled into a half-cell with sodium metal, the voltage range was tested from 1.5 to 4.3 V. The reversible specific capacity was 105 mAh / g, which is significantly lower than that of the material prepared in this invention.
[0135] Comparative Example 2
[0136] In this comparative example, the objective is to synthesize fluorinated iron phosphate material using conventional sodium fluoride as the fluorine source, and to compare its performance with that of the fluorinated iron phosphate material prepared in this invention.
[0137] First, weigh 0.05 mol ferrous oxalate dihydrate, 0.10 mol ferric phosphate dihydrate, 0.10 mol sodium dihydrogen phosphate, 0.10 mol sodium fluoride, and 5 g glucose monohydrate, and disperse them in 400 mL of deionized water. The mixture was then milled using a sand mill at 2000 rpm for 6 hours. The slurry was then removed and spray-dried while stirring. The inlet air temperature was 220°C, the outlet air temperature was 80°C, the rotary atomizer speed was 18000 rpm, and the peristaltic pump feed rate was 8.0 mL / min. The dried particles were collected and heated to 500°C at a rate of 3°C / min in a tube furnace under a nitrogen atmosphere, held at 500°C for 10 hours, and then allowed to cool naturally.
[0138] X-ray diffraction patterns of the tested materials revealed the presence of numerous sodium iron phosphate and sodium iron pyrophosphate impurity phases, while the material obtained in this invention was a pure phase. X-ray fluorescence spectrometry analysis of the fluorine content showed that the fluorine content of the product in this example was only 20% of the initial feed. In contrast, the fluorine content of the product prepared in this invention is over 90% of the initial feed.
[0139] The active material used in this example was coated to prepare an electrode, which was then assembled into a half-cell with sodium metal. The voltage range was tested from 1.5 to 4.3 V, and the reversible specific capacity was 100 mAh / g, which is significantly lower than that of the material prepared in this invention.
[0140] In this case, the poor electrochemical performance was due to the low success rate of fluorine substitution; excess fluorine persisted as sodium fluoride, failing to form a product and thus reducing product purity. The presence of impurities significantly reduced capacity utilization, rate performance, and cycle life.
[0141] Table 1. Performance comparison of products from the examples and comparative examples.
[0142]
[0143] In summary, the performance differences between the embodiments mainly stem from the differences in physical parameters such as particle size, specific surface area, uniformity and thickness of the carbon coating layer, and electronic conductivity of the carbon coating layer caused by the differences in raw materials and synthesis methods.
[0144] Compared to the comparative example, the performance improvement in the embodiment is mainly due to the reduction in band gap after fluorine substitution, which improves the intrinsic electronic conductivity. Simultaneously, the higher PF bond energy enhances the structural stability of the material during charge and discharge, suppresses lattice distortion, and thus increases the sodium ion diffusion coefficient. The improved cycle life is attributed to a significant reduction (approximately 50%) in cell parameter changes during cycling, suppressing lattice mismatches that may occur during lattice contraction and expansion, thereby improving cycle life.
[0145] In summary, the cathode material (mainly sodium iron fluorinated phosphate pyrophosphate) prepared by this invention has a phase purity of ≥95%. Electrodes prepared using the cathode material coating provided by this invention are assembled with sodium metal to form a half-cell. The test voltage range is 1.5~4.3V, the specific capacity of the first charge at 0.1C is ≥122mAh / g, the specific capacity of the first discharge at 0.1C is ≥115mAh / g, the coulombic efficiency is ≥93.5%, the reversible specific capacity at 10C is ≥89mAh / g, and the capacity retention rate after 1C-1000 cycles is ≥98.8%.
[0146] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A sodium iron pyrophosphate cathode material with fluorophosphate, characterized in that, The cathode material includes an amorphous carbon coating layer and a sodium iron fluoride pyrophosphate core. The molecular formula of the sodium ferric fluoride pyrophosphate is Na. 4+z Fe 3-y (PO4)2P2O 7-x F 2x ; Where x takes values of: 0 < x ≤ 1, y takes values of: 0 ≤ y ≤ 0.15, and z takes values of: -0.4 ≤ z ≤ 0.4; The precursor of the sodium ferric pyrophosphate includes a sodium source, an iron source, a phosphorus source, a fluorine source, and a carbon source; the fluorine source is fluorophosphate or fluorophosphate containing one or more phosphorus-fluorine bonds.
2. The cathode material according to claim 1, characterized in that, The space group of the crystal structure of the sodium iron fluoride pyrophosphate is Pn21a, which belongs to the orthorhombic crystal system. The cell parameters are in the following ranges: 6.41Å≤a≤6.81Å, 10.61Å≤b≤11.01Å, 18.24Å≤c≤18.64Å, α=β=γ=90°; Where a, b, and c are the cell lengths along the three-dimensional coordinate axes, and α, β, and γ are the angles between each pair of them.
3. The cathode material according to claim 1, characterized in that, The fluorophosphate iron pyrophosphate sodium has the same basic structural framework and crystallographic symmetry as sodium phosphate iron pyrophosphate or its iron-deficient phase. The structure of the sodium iron fluoride phosphate pyrophosphate is that two fluorine atoms replace one oxygen atom in the pyrophosphate ditetrahedron.
4. The cathode material according to claim 3, characterized in that, The bonding characteristics of the sodium ferric fluoride pyrophosphate are as follows: fluorine atoms and iron atoms do not form direct bonds, but fluorine atoms form bonds with phosphorus atoms in the pyrophosphate group.
5. The positive electrode material according to claim 1, characterized in that, The mass fraction of the amorphous carbon coating layer is 1–5 wt.%.
6. A method for preparing the cathode material according to any one of claims 1 to 5, characterized in that, Specifically, the following steps are included: S1: Mix the precursor of sodium ferric fluoride pyrophosphate and prepare it into a powder; S2: The powder obtained in S1 is calcined at high temperature and then sieved to obtain sodium iron pyrophosphate cathode material.
7. The preparation method according to claim 6, characterized in that, The precursor of sodium iron pyrophosphate fluorophosphate includes sodium source, iron source, phosphorus source, fluorine source and carbon source; The molar ratio of sodium:iron:phosphorus:fluorine in the raw materials is 3.9-4.1:3-y:4:2x. The amount of carbon source added depends on the carbonization rate, ensuring that the mass fraction of carbon in the final product is 1-5 wt.%.
8. The preparation method according to claim 6, characterized in that, The process used in step S1 is one of the following: solid-phase ball milling, sol-gel method, and "liquid-phase sand milling + spray drying".
9. The preparation method according to claim 6, characterized in that, The specific steps of high-temperature calcination in step S2 are as follows: In the tube furnace, the gas atmosphere is controlled to be nitrogen, argon, or a hydrogen-argon mixture, the gas flow rate is 50-200 mL / min, the heating rate is set to 2-5℃ / min, the holding temperature is 450-600℃, and the holding time is 5-12 h; the cooling process is natural cooling, and the cooling rate is controlled to be ≤5℃ / min.
10. A sodium-ion battery, characterized in that, The battery comprises the positive electrode material according to any one of claims 1 to 5 or the positive electrode material prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Patent Citations
Sodium ferrous fluorophosphate / N-CNT composite positive electrode active material, preparation thereof and application of sodium ferrous fluorophosphate / N-CNT composite positive electrode active material in sodium ion battery
CN115275126A
Sodium-rich fluorine-doped ferric sodium pyrophosphate composite material as well as preparation method and application thereof
CN116281922A